A pedagogical device from rurality for the development of basic competences (2019)
This article presents the results of a strategy aimed at the development of basic skills, using trending aspects that involve school knowledge typical of the rural context. Relationships of knowledge and powers of both teachers and students were established, which allowed better communication and mutual meaningful learning, giving valuable elements that contributed to the achievement of the objective. The article exposes the creation and implementation of a pedagogical deviced directed to the eighth grade students of the “Marco Antonio Quijano Rico” Educational Institution of the rural sector of the Municipality of Sogamoso;Through the “research - action” methodology, apparently independent processes were unified which allowed the reflection and overcoming of problems inherent to the classroom in particular and significant contexts for students, a strategy that can be applied in similar contexts.